IBCOx_1 Do we really need to use staple line reinforcement to prevent leaks after sleeve gastrectomy?. (30th November 2022) - Alhamdani, A; Sufi, P; Parmar, C
Abstract: Introduction: While some of systematic reviews inform us about the superiority of the stapler line reinforcement (SLR) over no reinforcement to prevent leaks in sleeve gastrectomy, the First Report from the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program (MBSAQIP) with 188, 000 patients contradicts this with higher leak rates associated with SLR. The objective is to understand why the variation in the literature about the SLR in preventing leaks or not and how this relates to surgeon experience. Methods: Literature review was performed and analysed to identify the type of the SLR used or not. This was compared with the leak site, stomach thickness and type of stapler thickness height used. The surgeon experience was also taken into account. Results: The leak rates were mainly due to inappropriate use of the stapler colour (thickness) in relation to the SLR type and the stomach thickness. In one systematic review higher leak rates were found when inappropriate low staple height (blue stapler 1.8mm closure height) was used to include bovine SLR (1mm thickness) to staple the fundal area (1.5mm thickness). In another meta-analysis less leaks rates were noticed using the same buttressing material with a larger stapler (green or gold). Increase in surgeon experience was associated with decreased leak rate. Conclusion: The inappropriate use of the stapler height with the SLR contributes to the leak and can explain the variation in the literature. The surgeon experience associated with decrease leak rates.